Comparison of Hybridization Techniques in Chickpea. Issue 2 (3rd January 2017) - Stefaniak, Thomas; McPhee, Kevin
Abstract : Chickpea ( Cicer arietinum L.) flowers are difficult to hybridize. Optimizing hybridization techniques would improve breeding progress and enhance cultivar development efforts. The objective of this experiment was to evaluate four combinations of pollination methods in chickpea to give breeders insight into the usefulness of emasculating and/or hormone application to female flowers. The failure or successful generation of confirmed viable hybrids was the only response variable considered. The author made pollinations in two field environments and one greenhouse environment at Minot, ND, in 2014 and 2015. Results indicate that emasculation and hormone treatment do not improve manual hybridization in chickpea.